NEEDS ANALYSIS OF ENGLISH FOR MIDWIFERY PURPOSES AT MIDWIFERY ACADEMY OF HARAPAN MULYA PONOROGO - Hariyanto, Hariyanto; Joyoatmojo, Soetarno; Nurkamto, Joko; Gunarhadi, Gunarhadi (Sanata Dharma University Yogyakarta, 2022)
This study aimed at describing the need analysis of English for Midwifery Purposes. The study was conducted at Midwifery Academy of Harapan Mulya Ponorogo in February 2018. The respondents were 34 students and 7 lecturers. Data collected through a questionnaire that was given to the students. The interview was conducted with 7 midwife lecturers. Data analyzed descriptively. The results of the study revealed that most students (61.8% believe that English was very useful. Almost half of the respondents (38,2%) said that English was useful to communicate with foreigner patients. 41.2 % of respondents wanted to study English in order to succeed in getting a job in the future. 23% of the respondents suggested that English teaching should be emphasized on speaking skill. 18.8% of respondents wanted the English instructional materials consisted of Antenatal care, 15.3 % about therapeutic communication. Meanwhile, Need analysis based on teachers’ perception in many things have similarity with students’ perception. They were the usefulness of English, Emphasizing English materials and teaching process. Researchers suggested to the lecturer to design English teaching material that suits the needs of midwifery students.